Effect of the Functional Appliances on Skeletal, Dentoalveolar, and Facial Soft Tissue Characteristics - Doris Šimac Pavičić; Anđelo Svirčić; Boris Gašparović; Luka Šimunović; Sara Crnković; Višnja Katić (Applied Sciences, 2025)
This study aimed to evaluate the impact of Twin Block appliance therapy on skeletal, dentoalveolar, and facial soft tissue characteristics. The study included 18 participants with Class II skeletal malocclusion who were treated with the Twin Block appliance. Lateral cephalograms and 3D face scans were analyzed before and after therapy for each participant. Dependent t-test results showed a significant increase in the protrusion of the lower incisors (p < 0.001), proclination of the lower incisors (p = 0.021), SNB (p = 0.005), Ls:E (p = 0.040), mandibular length (p < 0.001), and soft tissue mandible length (p < 0.001) and a significant decrease in the ANB (p = 0.003), Wits (p = 0.001), ANPG (p = 0.001), overbite (p = 0.001), and the retrusion of upper incisors (p = 0.002). Twin Block therapy caused changes in skeletal and soft tissue characteristics. The increase in the SNB angle and mandibular length, accompanied by the decrease in the ANB and Wits values reduced the skeletal discrepancy. The reduction in the ANPG indicated an improvement in the skeletal profile. Additionally, the increase in the soft tissue mandible length and distance between the upper lip and E-line contributed to improved esthetic soft tissue profile characteristics.